Changes in nomenclature, virulence factors, and antifungal resistance of the genus Candida - Fernandes, Maria Alyce Albuquerque; Aguiar, Francisca Lidiane Linhares de; Coutinho, Maria Gleiciane Soares; Brito, Erika Helena Salles de; Coelho, Camila Gomes Virginio; Fontenelle, Raquel Oliveira dos Santos (Frontiers in Fungal Biology, 2025)
Some Candida species of clinical interest have undergone recent nomenclature changes. These yeasts have a high capacity to adhere to and infect host tissues, driven by their virulence factors, as well as by the incidence of antifungal resistance. This review aimed to analyze the taxonomic changes of the main species of clinical interest within the Candida genus, considering the clinical implications of their virulence factors and the main mechanisms of antifungal resistance. The research results allowed us to understand that the updated nomenclature of Candida species is essential to maintain the criteria that define a genus, organizing the species according to their phylogenetic and evolutionary characteristics. Understanding the virulence factors and resistance mechanisms of the different species of clinical interest helps us understand how infections are initiated and established, as well as how these same species behave to neutralize the action of antifungals. Therefore, integrating knowledge of taxonomy, virulence, and resistance profiles is crucial for effective strategies to control and treat fungal infections.